A porous glass fiber supported asphalt smoke suppressing modifier and a preparation method thereof

CN122483402BActive Publication Date: 2026-10-27BEIJING MUNICIPAL ROAD & BRIDGE BUILDING MATERIALGRP +5
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610885371.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-27
Estimated Expiration
2046-06-18

AI Technical Summary

Technical Problem

[0002]沥青凭借优良粘弹特性广泛用于道路铺装,实际工程多采用热拌工艺施工,沥青在高温熔融、热加工过程中极易释放大量沥青烟气,烟气内含苯系物、多环芳烃等有害挥发性组分,污染施工环境并危害施工人员健康

Benefits of technology

本发明利用化学键合方式将磷酸盐抑烟组分固定于多孔玻璃纤维表面,并与纳米碳酸钙复配联用,构建起化学抑烟与物理抑烟相结合的双重作用体系。在沥青受热过程中,锚定在纤维表面的磷酸盐可有效捕捉活性自由基、中断氧化链式反应,从源头减少TVOC、PM10、PM2.5等污染物生成,同时,纤维形成的三维网络结构及负载的纳米碳酸钙,依靠物理吸附与扩散阻隔作用捕集烟气组分;两类机制协同作用,大幅降低沥青拌合、摊铺阶段的烟气排放,改善施工现场环境,保护作业人员身体健康,符合交通领域绿色低碳发展理念。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122483402B_ABST
    Figure CN122483402B_ABST
Patent Text Reader

Abstract

The application discloses a kind of porous glass fibre load type asphalt smoke suppression modifier and preparation method thereof, it is related to road engineering technical field.The application is by chemical bonding mode phosphate component is immobilized on the surface of porous glass fibre, and is used in combination with double particle size nano calcium carbonate, constructs integrated collaborative smoke suppression system with physical adsorption and chemical inhibition function.The phosphate in modifier can quench active free radicals during the process that asphalt is heated, inhibit volatile pollutants and soot particle generation;With the adsorption barrier effect of fiber three-dimensional crosslinking network and nano calcium carbonate, effectively capture flue gas, significantly reduce the flue gas emission during asphalt construction.The modifier of the application is well compatible with asphalt matrix, can smoothly improve the high-temperature viscosity of asphalt, long-acting improve the comprehensive service performance of pavement, prolong the service life of road, adapt to the construction demand of green low-carbon road engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road engineering technology, and in particular to a porous glass fiber-supported asphalt smoke suppressant modifier and its preparation method. Background Technology

[0002] Asphalt is widely used in road paving due to its excellent viscoelastic properties. In actual projects, hot-mix construction is often used. During the high-temperature melting and hot processing of asphalt, a large amount of asphalt fumes are easily released. The fumes contain harmful volatile components such as benzene compounds and polycyclic aromatic hydrocarbons, which pollute the construction environment and endanger the health of construction workers.

[0003] Existing asphalt smoke suppressing additives generally have shortcomings: the smoke suppressing components have a single mode of action and low smoke suppression efficiency; moreover, conventional smoke suppressing additives tend to deteriorate the physical and chemical properties of asphalt after being added to it, resulting in a decrease in the high-temperature viscosity and high and low temperature performance of asphalt, which restricts the engineering application of environmentally friendly modified asphalt.

[0004] Therefore, developing modifiers that can effectively suppress smoke and simultaneously optimize the properties of asphalt while ensuring its original performance is a technical challenge that urgently needs to be addressed in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a porous glass fiber supported asphalt smoke suppressant modifier and its preparation method, so as to solve the problems existing in the prior art.

[0006] To achieve the above objectives, the present invention provides the following solution: One of the technologies of this invention is to provide a porous glass fiber supported asphalt smoke suppressant modifier, comprising porous glass fiber, and phosphate and dual-particle-size nano-calcium carbonate supported on the porous glass fiber; The phosphate is covalently fixed to the surface of the porous glass fiber; the dual-particle-size nano-calcium carbonate fills and adheres to the pores and surface of the porous glass fiber; The nano-calcium carbonate is composed of two types of nano-calcium carbonate with different particle sizes: the first type has a particle size of 1–20 nm, and the second type has a particle size of 21–100 nm.

[0007] Furthermore, in the nano-calcium carbonate used in this invention, the mass percentage of the first type of nano-calcium carbonate is 30% to 50%, and the mass percentage of the second type of nano-calcium carbonate is 50% to 70%.

[0008] Furthermore, the phosphate includes ammonium dihydrogen phosphate.

[0009] Furthermore, the porous glass fiber has a length of 1-5 mm, a diameter of 20-25 μm, and a porosity of 40-50%.

[0010] The second technical solution of the present invention provides a method for preparing the above-mentioned porous glass fiber supported asphalt smoke suppressant, comprising the following steps: (1) Phosphate loading: The porous glass fiber is immersed in the aqueous solution of the phosphate at 75-85℃ to achieve dehydration condensation; after the reaction is completed, it is washed until neutral and dried to obtain the fiber intermediate; (2) Nanoscale calcium carbonate loading: The fiber intermediate is loaded onto the dual-nanoscale calcium carbonate to fill the pores of the porous glass fiber, thereby obtaining the porous glass fiber-loaded asphalt smoke suppressant modifier.

[0011] The third aspect of this invention is to provide the application of the above-mentioned porous glass fiber supported asphalt smoke suppressant modifier in asphalt smoke suppression.

[0012] Furthermore, the dosage of the porous glass fiber supported asphalt smoke suppressant modifier is 1-3% of the asphalt mass.

[0013] The smoke suppression and performance enhancement effects of the porous glass fiber supported asphalt smoke suppressant of this invention are synergistically achieved by the three components of porous glass fiber, nano-calcium carbonate, and phosphate. The specific mechanism of action is as follows: The porous glass fiber surface is covered with a large number of active silanol groups. In an aqueous environment and under heating conditions, these silanol groups can undergo dehydration condensation reactions with phosphate ions dissociated from phosphate to form stable Si-OP covalent bonds. Simultaneously, the metal cations generated by phosphate ionization can bind to negatively charged sites on the porous glass fiber surface through electrostatic interactions. Phosphate molecules act as cross-linking nodes, connecting the porous glass fibers to each other and constructing a three-dimensional inorganic framework network within the asphalt matrix. This network can physically constrain the asphalt at low temperatures, improving the system's viscosity and structural stability, while also providing a stable interface for chemical smoke suppression reactions.

[0014] Nano-calcium carbonate loaded within and on the surface of PGF channels, with its high specific surface area and abundant mesoporous structure, can efficiently adsorb volatile organic small molecules such as benzene series compounds and polycyclic aromatic hydrocarbons produced by the thermal decomposition of asphalt by relying on van der Waals forces. Its hierarchical pore structure can prolong the diffusion path and residence time of volatile organic compounds, promoting secondary cracking or carbonization and deposition of organic compounds under high temperature environment, thereby reducing flue gas production from the source.

[0015] Phosphate components chemically bonded to the three-dimensional framework can exert a dual chemical smoke suppression effect when heated: firstly, they catalyze carbonization, guiding the dehydration and carbonization of flue gas precursors in asphalt, forming a dense carbon layer on the surface of the system, and preventing flue gas from escaping outward; secondly, they quench free radicals, capturing active free radicals generated during the oxidation and cracking of asphalt, interrupting the oxidation chain reaction, and inhibiting the formation of particulate matter and polycyclic aromatic hydrocarbons.

[0016] In summary, porous glass fiber plays a core role as a carrier and cross-linking framework, organically combining the physical adsorption of nano-calcium carbonate with the chemical catalytic effect of phosphate. The complementary advantages of each component ultimately achieve efficient and synergistic smoke suppression.

[0017] The present invention discloses the following technical effects: This invention utilizes chemical bonding to immobilize phosphate smoke-suppressing components on the surface of porous glass fibers, and combines them with nano-calcium carbonate to construct a dual-action system combining chemical and physical smoke suppression. During the heating process of asphalt, the phosphate anchored on the fiber surface can effectively capture active free radicals and interrupt the oxidation chain reaction, reducing TVOC and PM2.5 at the source. 10 PM 2.5 While pollutants are generated, the three-dimensional network structure formed by the fibers and the loaded nano-calcium carbonate capture flue gas components through physical adsorption and diffusion barrier effects. The two mechanisms work synergistically to significantly reduce flue gas emissions during asphalt mixing and paving, improve the construction site environment, protect the health of workers, and conform to the green and low-carbon development concept in the transportation sector.

[0018] Compared to traditional additives that easily cause abnormal fluctuations in asphalt viscosity, the modifier of this invention has good interfacial compatibility with the asphalt matrix. The three-dimensional cross-linked network formed within the system can steadily increase the high-temperature viscosity of asphalt and improve the asphalt mixing efficiency. This advantage effectively broadens the asphalt construction window, allowing the material to maintain good workability under different temperature and humidity conditions, and can meet the engineering requirements under complex working conditions.

[0019] Furthermore, the cross-linked network skeleton running through the asphalt matrix can constrain the high-temperature flow deformation of asphalt and alleviate low-temperature stress cracking, achieving a balanced optimization of the asphalt's performance in both high and low temperatures. The filling effect of nano-calcium carbonate further densifies the internal structure of the asphalt, preventing the intrusion of external media such as moisture and oxygen, and slowing down the aging rate of the asphalt. The overall structural stability of the material is significantly improved, ensuring not only the long-term stability of the modification effect but also allowing the asphalt pavement to maintain excellent performance during long-term service, effectively extending the road's service life and enhancing traffic safety. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the structure and physical-chemical synergistic smoke suppression mechanism of the porous glass fiber supported asphalt smoke suppressant of the present invention.

[0022] Figure 2 This is a comparison curve of the TVOC suppression effects of various embodiments and comparative examples of the present invention.

[0023] Figure 3 The graphs show the comparison of PM10 and PM2.5 suppression effects for each sample; (a) compares the PM10 suppression effect, and (b) compares the PM2.5 suppression effect.

[0024] Figure 4 Comparison of the microstructure of asphalt samples from different samples; (a)-(e) are, in order, Comparative Example 1, Example 1, Example 2, Example 3, and Example 3 after short-term aging at 163°C for 5 hours (aging-Example 3).

[0025] Figure 5 The image shows a comparison of the Fourier transform infrared spectra of different asphalt samples from Comparative Example 1 and Example 3.

[0026] Figure 6 The bar charts show the comparison of zero-shear viscosity and creep recovery performance of undisturbed and aged asphalt samples. (a) is a comparison chart of creep recovery performance of different samples, and (b) is a comparison chart of zero-shear viscosity of different samples. Detailed Implementation

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0029] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0030] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0031] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0032] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0033] In the following embodiments of the present invention, porous glass fiber with a length of 1-5 mm, a diameter of 20-25 μm, and a porosity of 40%-50% is selected as the carrier. The fiber uses silica as the main matrix and is naturally enriched with silanol groups on its surface, so there is no need for pretreatment processes such as acid washing and high-temperature activation.

[0034] In the following embodiments of the present invention, 70# matrix asphalt was purchased from Futai Asphalt Plant; porous glass fiber was purchased from Chongqing Heyuan Composite Materials Co., Ltd.; nano-calcium carbonate was purchased from Beijing Boyu High-Tech New Material Technology Co., Ltd.; and ammonium dihydrogen phosphate was purchased from Shanghai Ziyi Reagent Factory.

[0035] Example 1 This embodiment provides a porous glass fiber supported asphalt smoke suppressant modifier, and the preparation steps are as follows: (1) Phosphate surface loading: Prepare an aqueous solution of ammonium dihydrogen phosphate with a concentration of 0.5 mol / L. Completely immerse the porous glass fiber in the aqueous solution of ammonium dihydrogen phosphate and place it in a constant temperature water bath at 80℃. Stir at 300 rpm for 1.5 h to promote the dehydration condensation reaction between the silanol groups on the surface of the porous glass fiber and the phosphate ions. After the reaction was completed, the fiber sample was repeatedly rinsed with deionized water until the pH of the washing filtrate stabilized at 7 to remove unreacted salt impurities from the fiber surface. The cleaned fiber was then placed in a 60 ℃ forced-air drying oven and dried at a constant temperature for 1 h to obtain a fiber intermediate with surface-bonded phosphate loading.

[0036] (2) Dual-particle-size nano-calcium carbonate supported composite modification: Weigh the materials separately according to the mass ratio of porous glass fiber and compounded nano-calcium carbonate at 10:1. Mix the two types of nano-calcium carbonate with particle sizes of 1-20 nm and 21-100 nm at a mass ratio of 1:1 in advance, and add deionized water to make a paste to avoid the agglomeration of nanoparticles. Add the paste of compounded nano-calcium carbonate to the fiber intermediate and stir magnetically at 300 rpm for 30 min to make the calcium carbonate particles of different sizes adapt to the multi-level pore size of the fiber in sequence, uniformly adhere to the fiber surface and gradient fill the internal pore channels. Place the mixture in a 100 ℃ forced-air drying oven to dry and cure for 1 h to remove moisture and form a stable embedded structure, and obtain the fiber additive, which is the porous glass fiber supported asphalt smoke suppressant modifier.

[0037] The fiber additive prepared in this embodiment is added to 70# base asphalt at a dosage of 1% of the asphalt mass.

[0038] Example 2 The only difference from Example 1 is that the fiber additive is added to the 70# base asphalt at a dosage of 2% of the asphalt mass.

[0039] Example 3 The only difference from Example 1 is that the fiber additive is added to the 70# base asphalt at a dosage of 3% of the asphalt mass.

[0040] Comparative Example 1 The blank control group used pure 70# base asphalt directly, without adding any fiber or smoke-suppressing components.

[0041] Comparative Example 2 The only difference from Example 1 is that the fiber is not loaded with phosphate or nano-calcium carbonate, and is made of pure porous glass fiber doped at 2% of the asphalt mass.

[0042] Comparative Example 3 The only difference from Example 1 is that only dual-size nano-calcium carbonate is loaded, without phosphate, to obtain a single physical smoke-suppressing modified fiber, which is doped at 2% of the asphalt mass.

[0043] Comparative Example 4 The only difference from Example 1 is that only ammonium dihydrogen phosphate is loaded, without dual-particle-size nano-calcium carbonate, to prepare a single chemical smoke-suppressing modified fiber, which is doped at 2% of the asphalt mass.

[0044] Comparative Example 5 Unlike the stepwise bonding and loading process in Example 1, this comparative example does not involve phosphate impregnation, dehydration, condensation, or calcium carbonate paste-filling loading. Instead, it directly and physically dry-mixes unmodified virgin porous glass fibers, ammonium dihydrogen phosphate, and dual-particle-size composite nano-calcium carbonate according to the same raw material ratio as in Example 1, obtaining the composite powder through simple mechanical mixing. This composite powder is then incorporated into 70# base asphalt at a dosage of 1% of the asphalt mass.

[0045] To evaluate the effects of the modifier of this invention on the performance of asphalt pavement and its smoke suppression effect, a volunteer olfactory assessment method was used to classify the odor pollution intensity of each group of samples, and the penetration, softening point, and ductility at 10℃ of different groups of asphalt were tested. The odor pollution intensity classification criteria are shown in Table 1, and the blending schemes, test performance, and odor level results of each embodiment and comparative example are shown in Table 2.

[0046] Table 1 Table 2 As shown in Table 2, the test results indicate that the conventional technical indicators of asphalt exhibit a regular change after incorporating the fiber additive of this invention: the asphalt penetration decreases, the softening point increases significantly, and although the ductility decreases slightly, it still fully meets the requirements of road engineering performance specifications. Specifically, as the additive dosage increases from 0% (Comparative Example 1) to 3% (Example 3), the asphalt penetration decreases from 72 (0.1 mm) to 46 (0.1 mm), indicating that the consistency of the asphalt system increases and its high-temperature deformation resistance is effectively improved; the softening point gradually increases from 48.0℃ to 64.8℃, indicating that the high-temperature stability of asphalt is significantly enhanced; the ductility at 10℃ decreases from 100 cm to 85 cm, with a controllable decrease that meets engineering standards. The reason for this is that the additive can construct a three-dimensional cross-linked network skeleton structure within the asphalt matrix, effectively increasing the viscosity of the asphalt system and improving the fatigue damage resistance of asphalt. In summary, the additive of this invention not only imparts excellent smoke suppression and odor neutralization functions to asphalt but also synergistically optimizes the road performance of asphalt.

[0047] Meanwhile, the odor intensity of the asphalt samples in each group was graded and evaluated using a volunteer olfactory assessment method. The odor pollution level of each embodiment was no higher than Level II, with virtually no irritating odor; Comparative Example 1 had an odor level as high as Level V, with pungent smoke and severe pollution; Comparative Examples 3 and 4 both had an odor level of Level III, exhibiting only limited smoke suppression effects. Furthermore, Comparative Example 5 had an odor level of Level III, indicating a poorer smoke suppression effect compared to the loading process in Example 1, where the physical mixture was used. The experimental comparison shows that simply adding porous glass fiber or a single smoke-suppressing component did not achieve ideal odor reduction and smoke suppression effects; however, this invention, through a loading process, co-immobilizes dual-particle-size nano-calcium carbonate and phosphate on the surface of porous glass fiber, leveraging the synergistic effect of physical adsorption and chemical smoke suppression to achieve optimal smoke suppression and odor reduction effects.

[0048] To quantitatively evaluate the application effects of different smoke suppression materials, further studies were conducted on the effects of each group of samples on TVOC and PM2.5. 10 and PM 2.5 Experimental study on emission suppression mechanisms. Quantitative flue gas analysis was conducted using a closed, constant-temperature flue gas testing chamber. Equal amounts of asphalt samples from each embodiment and comparative example were weighed and placed inside the closed testing chamber. The heating temperature was controlled at 163℃ to simulate the high-temperature melting and processing conditions of asphalt. TVOC and PM2.5 levels were monitored online throughout the process. 10 PM 2.5 Real-time concentration.

[0049] Figure 2 This study compares the TVOC suppression effects of different smoke-suppressing materials. It can be seen that the composite-loaded fiber of this invention has a significant TVOC suppression effect; as the content of the composite-loaded fiber increases from 1% to 3% (Examples 1-3), the TVOC suppression effect shows a progressively increasing trend. At a 2% content, both the unloaded pure porous glass fiber (Comparative Example 2) and the porous glass fiber with single-loaded nano-calcium carbonate (Comparative Example 3) exhibit certain TVOC suppression capabilities; under the same 2% content condition, the porous glass fiber with single-loaded ammonium dihydrogen phosphate (Comparative Example 4) shows a better chemical smoke suppression effect than the physical smoke suppression effect of Comparative Example 3.

[0050] Figure 3 (a) Figure 3 (b) The effect of each sample on inhalable particulate matter PM2.5 10 and fine particulate matter (PM) 2.5 The inhibitory effects of the two methods show a highly consistent pattern. Similar to the inhibition pattern of TVOC, the inhibitory effect of Examples 1-3 on particulate matter increases with the increase of modifier dosage, exhibiting a clear dose-dependent characteristic; Figure 4Microscopic images visually demonstrate the distribution of glass fibers in the asphalt matrix, further confirming the aforementioned variation patterns. Meanwhile, the chemical smoke suppression effect of Comparative Example 4 is generally superior to the physical smoke suppression effect of Comparative Example 3. Notably, under the same 2% dosage condition, the pure porous glass fiber (Comparative Example 2) exhibits an even better particulate matter suppression effect than Example 1 with a low dosage. This phenomenon indicates that porous glass fibers can directly capture flue gas particulate matter through physical interception and pore adsorption, a function particularly prominent at low modifier dosages. Furthermore, as the composite-loaded fiber dosage increases, the synergistic effect of physical adsorption and chemical smoke suppression gradually becomes dominant, resulting in smoke suppression performance significantly exceeding that of pure porous glass fiber.

[0051] The high-temperature rheological properties of blank base asphalt (Comparative Example 1), modified asphalt of Example 3, and modified asphalt of Example 3 after short-term aging at 163℃ for 5 hours were tested using zero-shear viscosity (ZSV) at 60℃ and multi-stress creep recovery (MSCR) at 64℃. The test results are shown in [Figure Number]. Figure 6 Experiments show that incorporating the fiber-type environmentally friendly additive of this invention can significantly improve the high-temperature performance of asphalt; among them, Example 3 achieved a zero-shear viscosity of 1731 Pa•s and a creep recovery rate of 20.2%, which is a significant improvement compared to Comparative Example 1's 254 Pa•s and -2.09%. After aging, the zero-shear viscosity of the asphalt further increased, while the multi-stress creep recovery rate slightly decreased. The improvement in the asphalt's road performance is mainly attributed to the formation of Si-OP covalent bonds in the system. Figure 5 The characteristic absorption peak of Si-OP appearing in the Fourier transform infrared spectroscopy results also confirms the existence of this chemical bond at the microscopic level.

[0052] Analysis of the comprehensive test results shows that the differences in smoke suppression effects among different groups are essentially due to differences in microstructure and mechanism of action: phosphate mainly plays a leading role in chemical catalysis of smoke suppression, but its smoke suppression efficiency can only be fully released by relying on the three-dimensional cross-linked network structure constructed with porous glass fibers; this cross-linked framework also enhances the physical adsorption efficiency of nano-calcium carbonate; in addition, the physical interception and adsorption of porous glass fibers can independently capture smoke particles, forming multiple synergistic effects with the chemical smoke suppression mechanism, ultimately achieving efficient smoke suppression and simultaneously optimizing the performance of asphalt pavement.

[0053] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A porous glass fiber supported asphalt smoke suppressant modifier, characterized in that, It includes porous glass fibers, and phosphate and dual-size nano-calcium carbonate loaded on the porous glass fibers; The phosphate is covalently fixed to the surface of the porous glass fiber; the dual-particle-size nano-calcium carbonate fills and adheres to the pores and surface of the porous glass fiber; The dual-size nano-calcium carbonate is composed of two types of nano-calcium carbonate with different particle sizes: the first type of nano-calcium carbonate has a particle size of 1 to 20 nm, and the second type of nano-calcium carbonate has a particle size of 21 to 100 nm. In the dual-particle-size nano-calcium carbonate, the first type of nano-calcium carbonate accounts for 30% to 50% by mass, and the second type of nano-calcium carbonate accounts for 50% to 70% by mass. The porous glass fiber uses silica as the main matrix and its surface is naturally enriched with silanol groups. The porous glass fiber has a length of 1-5 mm, a diameter of 20-25 μm, and a porosity of 40-50%. The mass ratio of the porous glass fiber to the dual-particle-size nano-calcium carbonate is 10:

1.

2. The porous glass fiber supported asphalt smoke suppressant modifier according to claim 1, characterized in that, The phosphate includes ammonium dihydrogen phosphate.

3. The preparation method of the porous glass fiber supported asphalt smoke suppressant as described in any one of claims 1-2, characterized in that, Includes the following steps: (1) Phosphate loading: The porous glass fiber is immersed in the aqueous solution of the phosphate at 75-85℃ to achieve dehydration condensation; after the reaction is completed, it is washed until neutral and dried to obtain the fiber intermediate; (2) Nano-calcium carbonate loading: Weigh the materials according to the mass ratio of the porous glass fiber and the dual-size nano-calcium carbonate of 10:1; mix the two types of nano-calcium carbonate with particle sizes of 1-20 nm and 21-100 nm in a mass ratio of 1:1 in advance, add deionized water to make a paste to avoid the agglomeration of nanoparticles; add the paste-like compounded nano-calcium carbonate to the fiber intermediate, and stir magnetically at 300 rpm for 30 min, so that the different particle sizes of calcium carbonate particles are adapted to the multi-level pore size of the fiber in sequence, uniformly attached to the fiber surface and gradient filling the internal pore channels; place the mixed system in a 100 ℃ forced-air drying oven to dry and solidify for 1 h, remove moisture and form a stable embedded structure to obtain the fiber additive, which is the porous glass fiber loaded asphalt smoke suppressant modifier.

4. The application of the porous glass fiber supported asphalt smoke suppressant as described in any one of claims 1-2 in asphalt smoke suppression.

5. The application as described in claim 4, characterized in that, The dosage of the porous glass fiber supported asphalt smoke suppressant modifier is 1-3% of the asphalt mass.

Citation Information

Patent Citations

  • Low smoke halogen-free flame retardant reinforced nylon composite material and manufacture method

    CN103131175A

  • Compound smoke suppression asphalt for tunnel pavement paving and preparation method of compound smoke suppression asphalt

    CN114350166A